2023
DOI: 10.21203/rs.3.rs-3299268/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

New Thermal Decomposition Pathway for TATB

Keith D. Morrison,
Ana Racoveanu,
Jason S. Moore
et al.

Abstract: Understanding the thermal decomposition behavior of TATB (1,3,5-triamino-2,4,6-trinitrobenzene) is a major focus in energetic materials research because of safety issues. Previous research and modelling efforts have suggested benzo-monofurazan condensation producing H2O is the initiating decomposition step. However, early evolving CO2 (m/z 44) along with H2O (m/z 18) evolution have been observed by mass spectrometric monitoring of head-space gases in both constant heating rate and isothermal decomposition stud… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 24 publications
1
4
0
Order By: Relevance
“…Furazan ring formation is the primary reaction with most degradation compounds detected containing one or more furazan rings. In a concurrent report with this study, F2 and other TATB decomposition products and their nitro loss analogues are shown to play a role in the gas-phase and possibly the solid-phase thermal decomposition mechanism [46]. 4.…”
Section: Discussionsupporting
confidence: 51%
See 2 more Smart Citations
“…Furazan ring formation is the primary reaction with most degradation compounds detected containing one or more furazan rings. In a concurrent report with this study, F2 and other TATB decomposition products and their nitro loss analogues are shown to play a role in the gas-phase and possibly the solid-phase thermal decomposition mechanism [46]. 4.…”
Section: Discussionsupporting
confidence: 51%
“…Many thermal decomposition studies on TATB have detected components of reacted TATB, such as C 2 N 2 , C 4 N 4 O, and other higher m/z compounds [5,10,14,44,45] that could react with TATB to form rings and oligomers of higher MW than TATB. Gas-phase TATB degradation reactions observed elsewhere [46] detect the 2carbon and 4-carbon degradation compounds involved in these reactions, and possible mechanisms for how they are formed.…”
Section: Structure Of Compoundsmentioning
confidence: 93%
See 1 more Smart Citation
“…At least as much mass is converted to an insoluble semi-char that first evolves and then quickly converts to a final char composition near the time of the first exotherm (Figure 11 bottom). The yield of gaseous products exceeds the soluble products at all extents of conversion (Figure 13), and early detection of both nitrogen and carbon oxides suggests that auto-oxidation is important at a very early stage [55], which might indicate that it is as fast or faster as the furazan formation above 250 °C and is possibly related to the insoluble reactive residue that persists up to 45 min.…”
Section: Interrupted Heating Dsc Experimentsmentioning
confidence: 99%
“…Isotopic labeling in MS incrementally changes the mass (usually one/substitution), often moving analyte masses away from masses of common interferents and allows for easier monitoring of specific sites, particularly when low-molecularweight gases are produced. These high purity and substituted labeled compounds have been used in examining the thermal degradation process of TATB by all the spectroscopic techniques above [42][43][44].…”
Section: Spectroscopic Applications Of Isotopically Labeled Tatbmentioning
confidence: 99%